The inverse of this function is f(x) = [tex] \sqrt[3]{x - 6} [/tex]
You can find the value of any inverse function by switching the f(x) and the x value. Then you can solve for the new f(x) value. The end result will be your new inverse function. The step-by-step process is below.
f(x) = x^3 + 6 ----> Switch f(x) and x
x = f(x)^3 + 6 ----> Subtract 6 from both sides
x - 6 = f(x)^3 ----> Take the cube root of both sides
[tex] \sqrt[3]{x - 6} [/tex] = f(x) ----> Switch the order for formatting purposes
f(x) = [tex] \sqrt[3]{x - 6} [/tex]
And that would be your new inverse function.